C++ and Algorithmic Thinking for the Complete Beginner. - Aristides Bouras; PACKT (GB: Packt, 2024)
Dive into the essentials of C++ and algorithmic thinking with this book. This comprehensive guide is perfect for newcomers looking to build a strong foundation in programming and problem-solving. Key Features Comprehensive introduction to C++ programming and detailed explanations of algorithmic concepts. Step-by-step setup of development environments, with practical exercises and real-world examples. In-depth coverage of control structures, and visual aids such as trace tables and flowcharts. Book Description Embark on your programming journey with a thorough introduction to how computers work, setting the stage for understanding C++ and its applications. This course begins with the basics, including setting up your development environment and installing necessary software packages. As you progress, you'll delve into fundamental algorithmic concepts, variables, constants, and handling input and output efficiently. As you build your knowledge, the course introduces more complex topics such as sequence control structures, decision-making processes, and loop control structures. You will learn to manipulate numbers, strings, and understand the intricacies of operators through practical exercises and real-world examples. Visual aids like trace tables and flowcharts will help you visualize the flow of your programs and improve your debugging skills. Towards the end of the course, you'll explore advanced topics such as arrays, data structures, subprograms, and an introduction to object-oriented programming. By the conclusion, you will also gain insights into file handling and advanced algorithmic strategies. Each chapter is designed to build on the previous one, ensuring a cohesive and comprehensive learning experience that equips you with the skills needed to excel in C++ programming and algorithmic thinking. What you will learn Understand how computers and programming languages work. Master the basics of C++ and integrated development environments. Develop and debug algorithms effectively. Manipulate variables, constants, and data structures. Implement control structures to manage program flow. Create and use subprograms to optimize code. Who this book is for This course is designed for complete beginners with no prior programming experience, making it ideal for a wide range of learners. High school students, college students, and self-taught programmers will find this course particularly useful. It's also suitable for professionals looking to transition into a programming role or enhance their technical skill set. Educators seeking a structured curriculum for teaching C++ can benefit from the course material. Basic computer literacy is recommended, but no prior knowledge of programming is required.
Data in extended ASCII character set.
Mode of access: Internet.